The Impact of Governance Application on Achieving Strategic Objectives: A Case Study of Profitable Organizations in the Kingdom for the Year 2023-2024 - Natheer, Hanan Abdullah; Al-Tuwayjiri, Ahmad Abdulaziz (Journal of Economic, Administrative and Legal Sciences, 2025)
The governance is currently witnessing a significant and noticeable development that includes all organizations in the Kingdom, both profitable and non-profit as well. This is because with the complexity of the work environment in its modern global economic form, these organizations have turned to governance because of its positive role in directing organizational strategies. This is why this Research on the impact of applying governance on achieving the strategic goals of for-profit organizations, by seeking to answer the following question: What is the impact of applying governance on achieving the strategic goals of for-profit organizations?: By using the descriptive correlational approach, the research reached a set of results that answer this question, the most important of which is: that the principle of participation in the principles of governance came to a high degree, as the general average of the dimension was equal to (4.05), and the degree of agreement (I agree), with a standard deviation of ( 1.28), which is a high value that indicates the varying opinions of the study sample members, that the principle of evaluation is one of the principles of governance to a high degree, as the general average of the dimension was equal to (3.80), and the degree of approval (I agree), with a standard deviation of (1.06), It is a high value that indicates the differences in the opinions of the study sample members. The principle of effectiveness was a very high degree of governance, as the general average of the dimension was equal to (4.48), and the degree of agreement (strongly agree), with a standard deviation of (0.50), which is a low value indicating Despite the homogeneity of the opinions of the study sample members, the strategic vision in setting strategic goals came at a high degree, as the general average for the dimension was equal to (2.99), and the degree of agreement (I agree), with a standard deviation of (1.77), which is a high value that indicates the discrepancy in the opinions of the sample members.
Keywords: governance; profit organizations; strategic objectives